Exploring the Nyorong Tradition as a Source of Contextual Science Learning in Secondary Education - Siska Afrilianti; Mahrus Mahrus; Rangga Adianata; Deyan Eka Tenggara (Indonesian Journal of Educational Innovation, 2026)
Contextual science learning is essential for enhancing students’ understanding by linking scientific concepts to real-life experiences. This study aims to explore the Nyorong tradition of the Samawa community as a contextual learning resource for science education through an ethnoscience approach. A qualitative descriptive method was employed, with data collected through observations, semi-structured interviews with four community members, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The results show that the Nyorong tradition comprises stages such as preparation, the delivery procession, and the symbolic handover, which embody educational values, including responsibility, cooperation, mutual assistance, social solidarity, and respect for cultural norms. In addition, these activities are closely related to scientific concepts such as force, work and energy, motion, energy transformation, and simple machines. It can be concluded that the Nyorong tradition has strong potential as a culturally relevant resource for contextual science learning. The findings imply that integrating local cultural practices into science instruction can support meaningful learning, strengthen conceptual understanding, and promote students’ character development.